Penerapan Model Pembelajaran Quantum Learning Untuk Meningkatkan Proses Belajar Reading Comprehension pada Bahasa Inggris - Muhammad Amran; Muhammad Asrul Sultan; Indah Choirunnisa (STKIP Andi Matappa Pangkep, 2024)
This research was motivated by the low learning achievement of reading comprehension in English for grade V students at UPTD SDN 47 Parepare. This research is classroom action research (PTK) which objective to find out the application of the Quantum Learning Model in the Reading Comprehension in English for grade V UPTD SD Negeri 47 Parepare and to find out learning achievement in the process of implementing the Quantum Learning Model in the Reading Comprehension in English for grade V UPTD SD Negeri 47 Parepare. The approach used in this achievement is a qualitative approach. The data analysis technique used is a qualitative analysis technique. Based on the data obtained during the implementation of cycle I, teacher activities were at sufficient qualifications (C), student activities were at insufficient qualifications (K) and students' reading comprehension were at sufficient qualifications (K). In the implementation of cycle II, teacher activities were at Good qualifications (B), student activities were at Good qualifications (B) and students' reading comprehension were at Good qualifications (B).